Pengembangan Inovasi Pengolahan Tahu Untuk Meningkatkan Nilai Jual Produk Di Desa Betro - Dimas Ganda Permana Putra; Herlambang Prihandoko; Syafa Maudina Nur Fitri; Fitri Linda Sari; Elisabeth Sriwilujeng; Inun Widiastuti; Ragil Tri Karle; Laila Dewi Romadhoni; Muhammad Syahrul Yusuf; Rika Nur Anggraini; Fara Aulia Rosanti; Bilsoni Putra Indartin; Rifqi Ali Efendi; Febriyanti Budi Retnowati; Tri Yuli Ferawati; Vriska Putri Angely; Yoga Pratama Aji; Mochammad Solichudin; Eki Lewandika Wicaksono; Dhimas Fajar Novianta; Mochamad Alfiansyah Sannanu; Galong Gebrael Jaball Othsmar; Fery Arjuna Lanisky; Faisal Sigit Novanto; Therta Galih Pamungkas (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
Mayjen Sungkono University Group 17 Thematic Science KKN activities are located in Betro Village. Betro Village has great potential in processing tofu, with the abundance of soybean raw materials and the skills of its people, making their local tofu products widely sought after. Betro Village has more than 10 white tofu factories that are still operating today. Betro Village also has a factory that produces tofu that has been fried and is ready to be sold. This research focuses on developing tofu processing innovations which aims to design innovative solutions to increase the selling value of tofu products by identifying the potential and needs of the local market in Betro Village. This activity aims to provide experience and as a learning process to explore village potential which can have a positive impact on the village economy.